PERBANDINGAN TINGKAT KEBUGARAN JASMANI ANTARA SISWA BERSEPEDA DAN JALAN KAKI KE SEKOLAH (STUDI PADA SISWA KELAS VIII SMP NEGERI 2 DEKET) - WAHYU SATRIO UTOMO, M. (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Advances of technology have positive and negative impact for human life. Its positive impact that techonology can simplify human in fulfill all their needed. Whereas its negative impact is declining level of physical fitness for human, no exception for students in education. The student’s physical fitness are affected by student activities in everyday, both in school and outside of school. At school, physical fitness of student can be maintained and enhanced through Penjasorkes lesson. Meanwhile, outside of school, student can follow sports is in the home environment. In addition to the daily activities of students when biking and walking to and from school are often found in 2nd Deket’s State Junior High School also can affect students' level of physical fitness. The research aims was to compare the physical fitness level of 8th students in 2nd Deket’s State Junior High School that biking and walking to school. The research design using comparative. The populations were used number of 132 of 8th students  in 2nd Deket’s State Junior High School. As for its sample retrieval by using simple purposive sampling from total population including fourth classes (VIIIA, VIIIB, VIIIC and VIIID) so obtained a sample size = 20 students were divided into 2 groups: biking group and walking groups each of 10 students. While the research instrument using questionnaires, tests MFT. Data analysis using independent sample t-Test. Based on result of research,  significant value (P Value) is greater than alpha value = 5% or 0.05 in the other words Sig > α (0,100 >  0,05) so resolved H0  is accepted. Means that no  significant differences between physical fitness level of 8th students  in 2nd Deket’s State Junior High School who biking and walking at school. Students who biking at school have physical fitness level amount 28,170. While students who walking at school have physical fitness level amount 32,500. So, between students who biking and walking to school only have physical fitness level differences amount 4,33. Keywords : Physical Fitness, Multistage Fitness Test (MFT), Students